(untitled) (International Seven Journal of Multidisciplinary, 2023)
This article explores advanced strategies for operational expenditure (OPEX) planning in multinational environments, emphasizing the integration of strategic cost management, digital forecasting, and adaptive governance mechanisms. In the context of increasing globalization, volatile markets, and regulatory complexity, effective OPEX planning requires balancing global standardization with local flexibility. By combining activity-based costing, driver-based budgeting, rolling forecasts, and scenario analysis, multinational corporations can enhance resource allocation, improve responsiveness to market dynamics, and reduce financial uncertainty. The study also highlights the importance of data integration, digital platforms, and interorganizational cost transparency in achieving operational excellence. Empirical evidence from recent academic and practitioner research demonstrates that organizations employing advanced, data-driven OPEX planning achieve greater cost efficiency and strategic resilience across global operations.